2008
DOI: 10.1007/s00468-008-0278-8
|View full text |Cite
|
Sign up to set email alerts
|

Desiccation tolerance acquisition in developing beech (Fagus sylvatica L.) seeds: the contribution of dehydrin-like protein

Abstract: The acquisition of desiccation tolerance (DT) in developing beech (Fagus sylvatica L.) seeds and the role of a dehydrin protein in this process were investigated. DT was determined by measurement of electrolyte leakage and germination capacity after drying to 10-12% moisture content (MC). In addition to mass maturity, the presence of heat-stable proteins, dehydrin accumulation and the peak of ABA content were measured in relation to the acquisition of DT. Mass maturity was achieved at 16 weeks after flowering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 59 publications
1
17
0
1
Order By: Relevance
“…The desiccation tolerance of kapok seeds appears to be related to seed maturity. Similar results have also been reported in many plants, in which immature seeds/embryos are desiccation sensitive and mature seeds/embryos are desiccation tolerant (Huang et al, 2011;Kalemba et al, 2009). It has been reported that at later stages of seed development such as at the end of the seed-filling phase many orthodox species may still show damage on desiccation to very low MC levels (Ellis and Hong, 1994;Hong and Ellis, 1996).…”
Section: Resultssupporting
confidence: 79%
“…The desiccation tolerance of kapok seeds appears to be related to seed maturity. Similar results have also been reported in many plants, in which immature seeds/embryos are desiccation sensitive and mature seeds/embryos are desiccation tolerant (Huang et al, 2011;Kalemba et al, 2009). It has been reported that at later stages of seed development such as at the end of the seed-filling phase many orthodox species may still show damage on desiccation to very low MC levels (Ellis and Hong, 1994;Hong and Ellis, 1996).…”
Section: Resultssupporting
confidence: 79%
“…On the other hand, Poulsen (1993) and Poulsen and Knudsen (1999) classified them as orthodox. Recent data (Kalemba et al 2009) on the acquisition of desiccation tolerance in beech seeds during their maturation (mainly in relation to LEA protein accumulation with additional parameters such as mass maturity, germination capacity, ABA level and the ratio of heat-stable proteins accompanying this process) indicated a typical orthodox behavior of these seeds.…”
Section: Introductionmentioning
confidence: 97%
“…ABA plays several key roles in the regulation of a plant's life cycle and its environmental response (Hirayama and Shinozaki 2007). Regulation of seed dormancy and response to water deficit, specifically the regulation of stomata movement, seem to be the most characteristic (Trejo et al 1995;Kalemba et al 2009;Nambara et al 2010). It is worth noting that in both cases the mechanisms of biochemical defence against dehydration, characteristic for the action of virtually all stress factors, are activated.…”
Section: Introductionmentioning
confidence: 99%